Nested Variant of Urothelial Carcinoma - Anthony Kodzo-Grey Venyo (Advances in Urology)
Background. Nested variant of urothelial carcinoma was added to the WHO’s classification in 2004. Aims. To review the literature on nested variant of urothelial carcinoma. Results. About 200 cases of the tumour have been reported so far and it has the ensuing morphological features: large numbers of small confluent irregular nests of bland-appearing, closely packed, haphazardly arranged, and poorly defined urothelial cells infiltrating the lamina propria and the muscularis propria. The tumour has a bland histomorphologic appearance, has an aggressive biological behaviour, and has at times been misdiagnosed as a benign lesion which had led to a significant delay in the establishment of the correct diagnosis and contributing to the advanced stage of the disease. Immunohistochemically, the tumour shares some characteristic features with high-risk conventional urothelial carcinomas such as high proliferation index and loss of p27 expression. However, p53, bcl-2, or EGF-r immunoreactivity is not frequently seen. The tumour must be differentiated from a number of proliferative lesions of the urothelium. Conclusions. Correct and early diagnosis of this tumour is essential to provide early curative treatment to avoid diagnosis at an advanced stage. A multicentre trial is required to identify treatment options that would improve the outcome of this tumour.